Electricity market integration and the impact of unilateral policy reforms - Luigi Grossi; Sven Heim; Kai Hüschelrath; Michael Waterson (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
The harmonization and integration of separate national energy markets to an interconnected internal European market is a top priority of the European Commission. However, as energy policy largely remains subject to national sovereignty, a higher degree of integration can cause unilateral national policies to harm interconnected markets. We investigate the impact of two distinct national reforms in Germany - the phase-out of nuclear power plants after the Fukushima incident and the expansion of renewables promoted by fixed feed-in tariffs and unlimited priority feed-in - on neighbouring countries. We find that the phase-out triggered price increases of up to 19 percent in neighbouring countries whilst the renewable energy support schemes caused a price decrease of up to 0.17 percent for each percent of additional generation from German renewables. We also apply a novel approach to estimate the degree of market integration and find large differences between neighbouring countries in a range from 14 percent to 99 percent. Our findings point up the need for increased efforts to harmonize national energy policies, but also the need to consider the impact of unilateral environmental measures on other countries' supplies in the context of a partially integrated and partly unilateral system.
urn:nbn:de:bsz:180-madoc-405861
Keywords: L51; L94; Q41; Q48; Q54; 330; Energy; Electricity; Market Integration; Nuclear Phase-Out; Renewables